Investigation of Classical Systems with Complex Energy in the Field of Quantum-Classical Correspondence (Global Journal of Science Frontier Research, 2018)
Classical mechanics and quantum mechanics contradict each other, and both are essential to explain the phenomena of the exclusively different realm of nature. On the other hand, Bohr's correspondence principle shows classical mechanics is the somewhat approximate version of quantum mechanics. Classically a particle with negative energy i. e. V E < is not allowed go through a forbidden region or disappearing from one well to another well. This paper gives the numerical studies for the trajectory of the particle in a double-well potential and presents quantum mechanical behavior such as tunneling in the complex plane for different energies. Our findings provide a route to solve the classical system with complex energy.
Keywords: double-well potential; complex energy; complex trajectory; PT-symmetry; tunneling